Berbagai Kajian Penelitian Fleksibilitas Psikologis : Tinjauan Literatur - Pramesti, Maulida Amalia; Hayati, Elli Nur; Bashori, Khoiruddin (Universitas Muhammadiyah Metro, 2024)
Psychological flexibility is a variable that has gained a lot of attention in recent years within psychology. Psychological flexibility refers to the ability to face and stay connected to this moment from time to time in any situation and to respond effectively to emotional experiences, including difficult or unpleasant ones, according to the values and goals of life. Psychological flexibility is a concept that has been studied across various research domains. This article aims to explore the fields of psychological flexibility research in a decade. The research data of psychological flexibility gathered through the database called Science Direct and popular article’s search engine called GoogleScholar. There are seven fields related to psychological flexibility research in a decade. All of these results will be discussed in this article.